2007
DOI: 10.1186/1471-2474-8-46
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of non-specific musculoskeletal pain in preteens and early adolescents: a prospective 1-year follow-up study

Abstract: Background: Musculoskeletal pain symptoms are common in children and adolescents. These symptoms have a negative impact on children's physical and emotional well-being, but their underlying aetiology and risk factors are still poorly understood. Most of the previous cohort studies were conducted among mid and/or late adolescents and were mainly focused on a specific pain location (e.g. low back pain or neck pain). The purpose of this study is to estimate occurrence of new-onset pain symptoms, in all musculoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 47 publications
7
75
0
13
Order By: Relevance
“…A maior prevalência de dores atuais foi referida pelo sexo masculino em nosso estudo, diferindo dos resultados de Taimela et al 10 ; ElMetwally et al 18 e Gareth et al 22 que verificaram maiores prevalências de lombalgia e DME no sexo feminino. Relacionamos este fato ao número de crianças estudadas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A maior prevalência de dores atuais foi referida pelo sexo masculino em nosso estudo, diferindo dos resultados de Taimela et al 10 ; ElMetwally et al 18 e Gareth et al 22 que verificaram maiores prevalências de lombalgia e DME no sexo feminino. Relacionamos este fato ao número de crianças estudadas.…”
Section: Discussionunclassified
“…Vários fatores investigados vêm sendo associados a estes sintomas: sexo, idade, medidas antropométricas, aspectos psicossociais e comportamentais e hábitos posturais em situação de vida diária [9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Some studies reported that, physical activity increases the risk of lower back 12) , lower limb 13,14) , traumatic 15) , overall musculoskeletal pain 16) , and widespread pain 17) , whereas others reported the opposite, suggesting that physical activity reduces the risk of back pain 18,19) . Additionally, whether or not a non-linear dose-response relationship exists was uncertain.…”
Section: Dose-response Relationship Between Sports Activity and Painmentioning
confidence: 99%
“…For example (Vikat et al, 2000), neck/shoulder pain is related to exercise among adolescents. El-Metwally et al (2007) identified vigorous exercise as a risk factor for traumatic musculoskeletal pain in preteens and early adolescents.…”
Section: Introductionmentioning
confidence: 99%